Tetragonopterinae (Cypriniformes, Characoidei, Characidae) capturados na Bacia do rio Ivaí, Estado do Paraná, Brasil - Parra-Muro, João (1980)
A study of five species of the Tetragonopterinae, family Characidae, is presented. The study material was collected at Rio Ivaí Basin, Paraná State, Brazil. The specimens obtained were studied at the Setor de Ictiologia, do Departamento de Vertebrados, do Museu Nacional, da Universidade Federal do Rio de Janeiro. Characters for higher taxa were given, and the synonimy was determined from Cypriniformes to species level. Distinguishing characteres between the two subspecies of Astyanax Baird & Girard, 1854 occuring the more frequently: Astyanax bimaculatus bimaculatus (Linnaeus, 1758) and Astyanax fasciatus fasciatus (Cuvier, 1819) were determined.